Comparison of In-situ and Numerical Shear strength analysis of Sandstone at Nalagad Hydropower Site - Basyal, Yubraj; Bist, Sushant; Yadav, Santosh Kumar (International Journal on Engineering Technology, 2025)
The shear strength of rock is a critical factor influencing the stability and safety of hydropower structures, particularly in underground powerhouse sites. This study investigates the shear strength behavior of sandstone at the underground powerhouse site of the Nalagad Hydropower Project through a comparative analysis of in-situ direct shear tests and numerical simulations performed in Abaqus/CAE 2020. A dynamic explicit approach with quasi-static conditions is employed to simulate stress distribution. Additionally, a mesh sensitivity analysis is conducted to evaluate the influence of element size on numerical shear strength predictions. The results indicate that the numerical model converges at a 20 mm mesh size, ensuring accuracy without excessive computational cost. In in-situ testing, the shear stress of sandstone was measured as 1.15 MPa and 1.80 MPa under normal stresses of 0.25 MPa and 0.65 MPa, respectively. Corresponding numerical modeling results yielded shear stresses of 1.10 MPa and 1.47 MPa under the same normal stress conditions. This indicates that the numerical model underpredicted shear stress values by approximately 4.3% at 0.25 MPa and 18.3% at 0.65 MPa compared to in-situ measurements. The observed discrepancies highlight the influence of material heterogeneity, boundary conditions, and constitutive model assumptions in numerical simulations. This research paper helps to understand the shear behavior of sandstone under specific loading condition and contribute in rock engineering. The paper can be useful for model enhancement and future research. The paper only focuses on shear behavior of sandstone but future research can be extended to other rock masses.